When Islamism and Pop Culture Meet: A Political Framing of the Movie "212: The Power of Love" - Akmaliah, Wahyudi (Studia Islamika, 2020)
This article examines the film 212: The Power of Love, which has been perceived as apolitical in political circumstances, and which was explicitly endorsed by new religious authorities. By critiquing the notion of Post-Islamism employed by scholars, this paper argues for the concept of Pop-Islamism, which emphasizes the contribution of political agents outside of political parties. I consider the following three questions: What is the primary reason behind creating a film in the context of the 212 movements? How does it deal with the event? What kind of Islam has been represented? This article argues that the medium of film is used to legitimize accusations of blasphemy made against Ahok through a singular interpretation of events, which represent Islam as a peaceful and tolerant religion. Subsequently, the film obscures select facts and issues to conceal the connection between the 212 movement and electoral politics in Jakarta. It does so by framing those issues apolitically in the context of increased Islamization in Indonesia.